The Influence of Team Fault Zone on Team Effectiveness : The Moderating Effect of Paradoxical - Wang, Haixi; Xu, Zhijian (Journal of Modern Learning Development, 2023)
The research on the relationship between team fault zone, interactive memory system and team efficiency. In order to gain advantages in the increasingly fierce market competition, it has gradually become one of the main work forms adopted by the enterprise to complete the work tasks. This paper is based on information processing theory, social cognitive theory, social exchange theory, A research model describing the relationship between team fault zone, interactive memory system, paradoxical leadership behavior and team efficiency was constructed, After the basic conceptual model and proposing the research hypothesis, Finally, 502 questionnaires from 107 project teams, valid questionnaire data, Through the empirical research methods, it is found that: (1) the social classification fault zone has a significant negative impact on both the interactive memory system and the team efficiency; (2) The information cognitive fault zone has a significant positive impact on both the interactive memory system and the team efficiency; (3) The interactive memory system plays a significant intermediary role in the relationship between the two types of fault zones and team performance; (4) Paradoxical leadership behavior has a significant and positive impact on the relationship between social classification fault zone, information cognition fault zone and team efficiency.